Olive oil glycerolysis with an immobilized lipase Candida antarctica in a solvent free system - A. K. Singh; M. Mukhopadhyay (Grasas y Aceites, 2012)
In the present work, the solvent free lipase glycerolysis of olive oil for the production of monoglyceride (MG) and diglyceride (DG) with an immobilized Lipase B Candida antarctica was studied. The experiments were performed in batch mode by varying different process parameters. The Results showed that the MG and DG yields were dependent on operating conditions such as time, temperature, glycerol/ oil molar ratio, enzyme concentration and the water content in glycerol. The optimum operating time for maximum MG, 26 wt% and DG, 30 wt% production was 3h. The initial reaction rate was studied by varying different process parameters for 1h. The initial reaction rate increased at 30 °C temperature, 2:1 glycerol/oil molar ratio, 3.5% (w/w) water content in glycerol and 0.015g of enzyme loading. Comparative data for MG and DG yields for different oils and enzyme combinations were presented.